English Teaching in Agricultural Universities (Zien Journal of Social Sciences and Humanities, 2023)
This study looked into the quality of English instruction in agricultural universities in Uzbekistan. English is a supplemental subject offered in agricultural universities to equip students for global communication issues. Following graduation and post-graduation, students prepare to serve in a variety of local and worldwide organizations and corporations. Because English is the primary medium of communication in the business, English demands additional emphasis in addition to students' subjective skills. Employers frequently advise candidates to improve their English language skills when recruiting. As a result, teaching and mastering English is an important priority for agricultural universities. The researcher focused on many stages of students' academic connection with English in this study, including students' academic competency in English upon admission, needs analysis, syllabus design, course aims as ESP, content quality, hours invested, and assessment.